(untitled) (Indian Journal of Child Health, 2019)
Background: Asthma treatment guidelines recommend that inhaled corticosteroids (ICS) can be stopped in children if they remain asymptomatic on its lowest dose. However, the effect of stopping steroids on their pulmonary function largely remains unknown. Objective: The objective of the study was to compare the lung function parameters of children with persistent asthma, who were treated with ICS for at least 1 year and are now remaining asymptomatic after stopping them for ?1 year (children who outgrew asthma), with the lung function parameters of children in same age group without asthma. Materials and Methods: The study design was cross-sectional comparative study, and it was conducted in the pediatric asthma clinic of a tertiary level teaching hospital in South India from August 2017 to July 2018. The study included 54 children in the age group of 6–18 years with asthma, nowremaining asymptomatic after stopping ICS for ?1 year and 54 children in same age group without asthma. Spirometry was done in both groups. Post-bronchodilator reversibility testing was done for children with asthma. Results: The median values of forced expiratory volume in one second (FEV1), FEV1%, FEV1/forced vital capacity (FVC) ratio, peak expiratory flow (PEF), PEF%, forced expiratory flow 25-75 (FEF25-75), and FEF25-75% were observed to be significantly lower in children who outgrew asthma symptoms, when compared with children without asthma. A statistically significant number of children who outgrew their asthma had FEV1% <80%, FEV1/FVC ratio <80%, PEF% <80%, and FEF25-75% <80% when compared to children without asthma. After inhalation of short-acting beta-agonist, 18 children (33.3%) who had outgrown asthma symptoms had FEV1 reversibility more than 12%. Conclusion: The pulmonary functions of children with bronchial asthma who were remaining asymptomatic for more than 1 year after stopping ICS were significantly lower than children without asthma.